The physical properties of sawdust briquette and the thermal performance of biomass briquette stove - Thuchayapong, Nat; Intagun, Weeranut (Food Agricultural Sciences and Technology, 2016)
The purpose of this research was to study the use of a biomass briquette stove instead of a Liquid Petroleum Gas (LPG) cooking stove. In this research, the biomass briquettes were made from sawdust with waste paper as a binder, and their physical properties were tested. Then, the biomass briquette stove was constructed and tested for its thermal effi ciency. From the experiments, it was found that the thermal effi ciency of the biomass briquette stove was 31.3 %. Furthermore, the biomass briquette stove and LPG cooking stove were compared for a cost analysis. From the comparison, the fuel cost per energy output of the sawdust briquette was signifi cantly lower than that of LPG. This showed that the stove was a good alternative to save energy and money.